ANALISIS CLUSTER UNTUK MENGELOMPOKKAN PENGGUNAAN KARTU PERDANA SELULER DI UNIVERSITAS BINA BANGSA : Survei Mahasiswa Jurusan Pendidikan Matematika - Ajeng Afifah Muhartini; Tanti Febriati; Sri Sukmawati (LPPM Universitas Bina Bangsa, 2022)
The development of technology and communication has led to increasing competition, especially in the field of marketing, one of which is in the cellular phone cards business. There are several companies that innovate in issuing cellular card products with their respective advantages to attract consumers' interest, be it the phone cards, postpaid cards or internet quota cards. In marketing segmentation, the decision to purchase starter packs by customers or buyers based on the benefits or benefits obtained is certainly different. The purpose of this study was to classify the types of starter packs used by students of the Mathematics Education Department at Bina Bangsa University based on their marketing. This research is a quantitative research with survey method with Cluster Analysis. Cluster analysis used is the Hierarchy Method using agglomerative grouping procedures. The results obtained in the calculation of the euclidean distance between Telkomsel Cards and Axis Cards is 542.76 while the euclidean distance between Telkomsel Cards and XL Cards is 486.34, for the euclidean distance between Telkomsel Cards and Three Cards is 671.31 while the euclidean distance between Telkomsel Cards and Indosat Cards is 809.13. The conclusion is that there are 2 clusters where the grouping of starter packs into 2 clusters has the composition or number of groups of each cluster. The minimum is cluster 1 which consists of only 1 starter card and the most is cluster 2 which consists of 5 starter cards